Pulmonary agenesis: two cases reported - Denis Yaraví Solano-Vázquez; Gabriel Gutiérrez-Morales; Francisco Cuevas-Schacht (Instituto Nacional de Pediatría, 2014)
Background: Pulmonary agenesis is a rare anomaly (1 in 15 000 live births) which consists in a total absence or severe hypoplasia of one or both lungs. The clinical spectrum of the unilateral agenesis could vary from early and severe respiratory distress, recurrent pneumonia to being an incidental finding. The prognosis is based on the presence of associated congenital abnormalities. Material and methods: We present two cases of unilateral pulmonary agenesis in patients at Tlaxcala's Children Hospital during 2012. Results: Report details the case of a one-month old boy with left pulmonary agenesis and interatrial communication and mild pulmonary arterial hypertension. He had two resolved pneumonia incidents. The other case was a one-month old girl with right pulmonary agenesis, associated to multiple heart malformations who evolved to respiratory failure, heart failure and death.Conclusions: Pulmonary agenesis is a rare anomaly. Its outcome and prognosis varies with the hemodynamics related to its location and associated malformations.